Anomalies of Pulmonary Circulation as a Cause of Hemoptysis: A Series of Unusual Cases and Review of the Literature - Kamini Gupta; Kavita Saggar; Amit Goyal; Avik Banerjee (Oman Medical Journal, 2015)
The expectoration of blood originating from the lower respiratory tract, called hemoptysis, is a common clinical condition with many potential etiologies. Massive hemoptysis is life threatening and needs urgent intervention. Multidetector computed tomography (MDCT) is a useful non-invasive imaging modality for the initial assessment of hemoptysis. Using MDCT with multiplanar reformatted images has improved the diagnosis and management of hemoptysis by providing a more precise depiction of bronchial and non-bronchial systemic arteries than conventional computed tomography (CT). In 95% of hemoptysis cases, the systemic arterial system is the origin of bleeding and pulmonary vascular anomalies are a rare cause. Among these, pulmonary arteriovenous malformation, hereditary hemorrhagic telangiectasia, and Osler-Weber-Rendu disease are well known entities. However, primary anomalies affecting pulmonary vessels in the mediastinum or diseases secondarily affecting the pulmonary vessels are unusual causes. Here we present three cases where patients had pulmonary vascular anomalies causing hemoptysis. These patients had decreased pulmonary arterial pressures leading to bronchial and systemic arterial hypertrophy and development of bronchopulmonary collaterals. Secondary CT signs in the parenchyma and mediastinum (mosaic attenuation, ground glass haze, subpleural interstitial thickening, and hypertrophied bronchial arteries) were similar in all patients. Hence, evaluation of the MDCT images for primary abnormality led to the diagnosis.